Exploring childhood cancer survivors' views about sex and sexual experiences -findings from online focus group discussions. (February 2016) - Jervaeus, Anna; Nilsson, Jenny; Eriksson, Lars E.; Lampic, Claudia; Widmark, Catarina; Wettergren, Lena
Abstract: Purpose: To explore childhood cancer survivors' views about sex and sexual experiences and, as an additional aim, their possible needs for care and support from health care professionals regarding sexual life. Methods: Written online focus group discussions were performed with survivors of childhood cancer, identified through the Swedish Childhood Cancer Registry; 133 (36%; aged 16–25) participated. Written text was analysed using qualitative content analysis. Results: The analysis resulted in one main category: Could my cancer experience have an impact on my sexual life? with four generic categories: Sex considered to be good, Feeling insecure and falling behind, Relating sex to a stable relationship and Concerns related to the physical body . In general, participants had not reflected on the possibility that their cancer experience could impact on sexual life. Sex was often considered to be something natural, important and taken for granted. However, thoughts and worries were expressed including being shy, feeling insecure and falling behind peers. Physical concerns included vaginal dryness and difficulties related to erection and reaching orgasm. Many participants stated that sexual issues had not been discussed with health care professionals, however, the need for such support differed. Conclusions: Many of the childhood cancer survivors' did not relate their sexual experiences to previous cancer treatment. However, problems were expressed, both of emotional and physical nature. Many participants stated that they had not received any information or support regarding sexual issues from health care professionals, why it is recommended to be regularly addressed in follow-up care. Highlights: 133 childhood cancer survivors participated in focus groups about sexual life. Many participants had not reflected over that the cancer experience could impact on sexual life. Thoughts and worries were expressed including being shy and feeling insecure. Physical concerns were expressed such as vaginal dryness and erectile dysfunction. Many participants had never discussed sexual matters with a health care professional.